Hukum Sebagai Alat Kontrol Sosial dan Sistem Supremasi Penegakan Hukum - Dewi Iriani (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2011)
Discourse about law as a tool of social control related to method and sociological discipline. A multidisciplinary approuch to the law is absolutely necessary when we discuss the law as an instrument of social control. One of the important things in this issue is that the law required to meet the concrete needs of the community, so the law goes effectively. Another important aspect after that is a supremacy of law aplication or the rule of law. The supremacy of law is necessary in order to realize the function of law as an instrument of social control to fully consider the sociological aspects of law enforcement.